Pharmacogenetic analysis of INT 0144 trial: association of polymorphisms with survival and toxicity in rectal cancer patients treated with 5-FU and radiation - Bohanes, Pierre; Ulrich, Cornelia (Clinical cancer research, 2015)
Purpose: We tested whether 18 polymorphisms in 16 genes (GSTP1, COX2, IL10, EGFR, EGF, FGFR4, CCDN1, VEGFR2, VEGF, CXCR2, IL8, MMP3, ICAM1, ERCC1, RAD51, and XRCC3) would predict disease-free survival (DFS), overall survival (OS), and toxicity in the INT0144 trial, which was designed to investigate different postoperative regimens of 5-fluorouracil (5-FU)-based chemoradiation (CRT) in locally advanced rectal cancers: Arm 1 consisted of bolus 5-FU followed by 5-FU protracted venous infusion (PVI) with radiotherapy; arm 2 was induction and concomitant PVI 5-FU with radiotherapy and arm 3 was induction and concomitant bolus 5-FU with radiotherapy. Experimental Design: DNA from 746 stage II/III rectal patients enrolled in the Southwest Oncology Group (SWOG) S9304 phase III trial was analyzed. Genomic DNA was extracted from formalin-fixed, paraffin-embedded (FFPE) tumor tissue. The polymorphisms were analyzed using direct DNA-sequencing or polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Results: GSTP1-Ile105Val (rs1695) was significantly associated with DFS and OS and its effect did not vary by treatment arm. The five-year DFS and OS were 53% and 58%, respectively, for G/G, 66% and 72% for G/A, and 57% and 66% for A/A patients. In arm 2, IL8-251A/A genotype (rs4073) was associated with a lower risk of toxicities (P = 0.04). The VEGFR2 H472Q Q/Q genotype (rs1870377) was associated with a higher risk of grade 3-5 proximal upper gastrointestinal tract (PUGIT) mucositis (P = 0.04) in arm 2. However, in arm 1, this genotype was associated with a lower risk of PUGIT mucositis (P = 0.004). Conclusion: rs1695 may be prognostic in patients with rectal cancer treated with adjuvant CRT. rs4073 and rs1870377 may exhibit different associations with toxicity, according to the 5-FU schedule. Clin Cancer Res; 21(7); 1583-90. ©2015 AACR.